Strategic management and business policy : globalization, innovation, and sustainability - Wheelen, Thomas L. (Pearson, 2018)
ISBN: 9781292215488 is a Global Edition of Strategic Management and Business Policy: Globalization, Innovation and Sustainability 15th Edition by J. David Hunger Thomas L. Wheelen Alan N. Hoffman Charles E. Bamford This ISBN 9781292215488 is Textbook only. It will not come with online access code. Online Access code (should only be purchased when required by an instructor ) sold separately at other ISBN. Global Edition (Paperback) has different cover page from Hardcover. It has the same edition, same title, and same authors. For courses in Strategic Management and Business Policy. Utilize a strategic management model to learn and apply key concepts through cases Picking up where the popular previous editions left off, Strategic Management and Business Policy: Globalization, Innovation and Sustainability, 15th Edition further sharpens and modernizes this classic text’s approach to teaching strategy with an emphasis on globalization, innovation, and sustainability. Throughout, the authors equip students with the strategic concepts they will need to know as they face the issues that all organizations must build upon to push their businesses forward. In this edition, Alan Hoffman and Chuck Bamford bring a fresh perspective to this extraordinarily well-researched and practically crafted lesson. Also included is a new chapter on Global Strategy, along with new vignettes and comprehensive, real-world case studies.